Surgical nonunion treatment of large-sized defects of femur and tibia based on the diamond concept - Sebastian Findeisen; Louis Mennerat; Thomas Ferbert; Lars Helbig; Tim N. Bewersdorf; Tobias Großner; Christian Schamberger; Gerhard Schmidmaier; Michael Tanner (Bone & Joint Open)
Aims: The aim of this study was to evaluate the radiological outcome of patients with large bone defects in the femur and tibia who were treated according to the guidelines of the diamond concept in our department (Centre for Orthopedics, Trauma Surgery, and Paraplegiology). Methods: The following retrospective, descriptive analysis consists of patients treated in our department between January 2010 and December 2021. In total, 628 patients were registered, of whom 108 presented with a large-sized defect (≥ 5 cm). A total of 70 patients met the inclusion criteria. The primary endpoint was radiological consolidation of nonunions after one and two years via a modified Lane-Sandhu Score, including only radiological parameters. Results: The mean defect size was 6.77 cm (SD 1.86), with the largest defect being 12.6 cm. Within two years after surgical treatment, 45 patients (64.3%) presented consolidation of the previous nonunion. After one year, six patients (8.6%) showed complete consolidation and 23 patients (32.9%) showed a considerable callus formation, whereas 41 patients (58.6%) showed a Lane-Sandhu score of 2 or below. Two years after surgery, 24 patients (34.3%) were categorized as Lane-Sandhu score 4, another 23 patients (32.9%) reached a score of 3, while 14 patients (20.0%) remained without final consolidation (score ≤ 2). A total of nine patients (12.9%) missed the two-year follow-up. The mean follow-up was 44.40 months (SD 32.00). The mean time period from nonunion surgery to consolidation was 16.42 months (SD 9.73) Conclusion: Patients with presentation of a large-sized nonunion require a structured and sufficiently long follow-up to secure the consolidation of the former nonunion. Furthermore, a follow-up of at least two years is required in order to declare a nonunion as consolidated, given that a significant part of the nonunions declared as not consolidated at one year showed consolidation within the second year. Moreover, the proven “gold standard” of a two-step procedure, so called Masquelet technique, shows effectiveness. Cite this article: Bone Jt Open 2024;6(1):26–34.